Philippine Performance Evaluation and Assessment Scheme (PPEAS): Experiences in Newborn Screening System Quality Improvement - Carmencita D. Padilla; Bradford L. Therrell; Karen Asuncion R. Panol; Riza Concordia N. Suarez; Ma. Elouisa L. Reyes; Charity M. Jomento; Ebner Bon G. Maceda; Jovy Ann C. Lising; Frederick David E. Beltran; Lita L. Orbillo (MDPI AG, 2020)
Newborn Bloodspot Screening (NBS) has existed for over 60 years, having been initiated by Guthrie in the U.S. In the Philippines, NBS was introduced in 1996 and later was supported by legislation. The NBS program now includes 29 conditions, covering 91.6% of the newborn population in 2019. Program growth and expansion necessitated development of a formal performance evaluation and assessment scheme (PEAS) for monitoring performance and for continuously improving quality. This study's objective was to present the development, implementation, and results to date of the Philippine Performance PEAS (PPEAS). Using the comprehensive listing of laboratory and non-laboratory elements in the model PEAS system in the U.S., PPEAS tools were developed for critical Philippine NBS system components: regional Department of Health (national health agency, Philippines) (DOH) offices (CHDs), NBS laboratories (NSCs), NBS specimen submitters (NSFs), and long-term case management centers (NBSCCs). Data generated from the various PPEAS have been periodically reviewed and analyzed for NBS system impact. PPEAS were developed to facilitate quality improvement at various levels of the Philippine NBS system. PPEAS identified successes, gaps, and challenges to be addressed by NSCs, NSFs, CHDs, and NBSCCs with the assistance of the Newborn Screening Reference Center and the Department of Health.